Eurasia’s Economic Union and ASEAN: Why Interaction Is Important - Amrebayev, Aidar (2016)
Members of the emerging Eurasian Economic Union (EEU) are reaching out to Southeast Asian countries to balance China’s growing influence in Eurasia. What are the implications for ASEAN?